Determinants of human hair mercury, blood mercury, blood selenium, and plasma omega-3 fatty acid levels within northern Canada - Sara Packull-McCormick; Mylène Ratelle; Mallory Drysdale; Michael M. Borghese; Michèle Bouchard; Ken D. Stark; Mary Gamberg; Heidi Swanson; Kelly Skinner; Brian D. Laird (International Journal of Hygiene and Environmental Health, 2026)

Interference of PFAS sorption on zeolites from natural water characteristics - Nathaniel P. Sheehan; Charles A. Ponge; Abe Pankratz; Justin M. Hutchison; Brian B. Laird; Nuong P. Nguyen; Mark B. Shiflett; Deepak Timalsina; Michael Zhuo Wang; Edward F. Peltier (Chemosphere, 2025)

Factors and mechanisms driving among-lake variability of mercury concentrations in a benthivorous fish in the canadian subarctic - Mehdi M. Aqdam; Jennifer L. Baltzer; Brian A. Branfireun; George Low; Mike Low; Brian D. Laird; Heidi K. Swanson (Chemosphere, 2025)

Environmental stressors and zoonoses in the Arctic: Learning from the past to prepare for the future - Emilie Andersen-Ranberg; Ingebjørg H. Nymo; Pikka Jokelainen; Anastasia Emelyanova; Solveig Jore; Brian Laird; Rebecca K. Davidson; Sonja Ostertag; Emilie Bouchard; Freja Fagerholm; Kelly Skinner; Mario Acquarone; et al. (Science of The Total Environment, 2024)

Human biomonitoring of dioxins, furans, and non-ortho dioxin-like polychlorinated biphenyls (PCBs) in blood plasma from Old Crow, Yukon, Canada (2019) - Ashlyn K. Simpson; Mallory Drysdale; Mary Gamberg; Ken Froese; Jeremy Brammer; Pierre Dumas; Mylène Ratelle; Kelly Skinner; Brian D. Laird (Science of The Total Environment, 2024)

Hexachlorobenzene and omega-3 fatty acid intake from traditional foods in the northern Yukon: A risk and benefit analysis - Mallory Drysdale; Mary Gamberg; Jeremy Brammer; Shannon E. Majowicz; Sara Packull-McCormick; Kelly Skinner; Brian D. Laird (Science of The Total Environment, 2024)

Human health and environmental risk assessment of metals in community gardens of Winnipeg, Manitoba, Canada - Teresa Senderewich; Doug Goltz; Jose Luis Rodriguez-Gil; Brian Laird; Ryan S. Prosser; Mark L. Hanson (Environmental Science and Pollution Research, 2024)

Micro-distribution of arsenic in toenail clippings using laser ablation inductively coupled plasma mass spectrometry: implications for biomonitoring - Jennie R. Christensen; Geriene O. LaBine; Janet S. Cheung; Renata Rosol; Asish K. Mohapatra; Brian Laird; Hing Man Chan (Environmental Monitoring and Assessment, 2024)

Mercury bioaccessiblity in freshwater fish species from northern Canada - Sara Packull-McCormick; Alicia Cowan; Ken D. Stark; Mike Low; Mary Gamberg; Heidi Swanson; Brian Laird (Science of The Total Environment, 2023)

Prenatal and concurrent blood mercury concentrations and associations with IQ in canadian preschool children - Sara Packull-McCormick; Jillian Ashley-Martin; Kavita Singh; Mandy Fisher; Tye E. Arbuckle; Bruce Lanphear; Brian D. Laird; Gina Muckle; Linda Booij; Elizabeth Asztalos; Mark Walker; Maryse F. Bouchard; et al. (Environmental Research, 2023)

Estimates, spatial variability, and environmental drivers of mercury biomagnification rates through lake food webs in the Canadian subarctic - Mehdi Moslemi-Aqdam; George Low; Mike Low; Brian D. Laird; Brian A. Branfireun; Heidi K. Swanson (Environmental Research, 2023)

Influence of glacial turbidity and climate on diatom communities in two Fjord Lakes (British Columbia, Canada) - Kathleen R. Laird; Cécilia Barouillet; Brian F. Cumming; Christopher J. Perrin; Daniel T. Selbie (Aquatic Sciences, 2021)

Heterogeneous response of diatom assemblages since ca. 1945 in lakes from boreal regions of northern Alberta and Saskatchewan, Canada - Kathleen R. Laird; Graham R. Mushet; Roger J. Flower; Alexander P. Wolfe; Brian F. Cumming (Journal of Paleolimnology, 2020)

Bottom-Up Forces Drive Increases in the Abundance of Large Daphnids in Four Small Lakes Stocked with Rainbow Trout (Oncorhynchus mykiss), Interior British Columbia, Canada - Graham R. Mushet; Kathleen R. Laird; Peter R. Leavitt; Stephen Maricle; Andrew Klassen; Brian F. Cumming (Ecosystems, 2020)
The introduction of salmonids into lakes of western North America for sport fishing is a widespread phenomenon. While numerous investigations have documented cascading trophic interactions upon the introduction of fish into naturally fishless systems, little research has been done to investigate the importance of natural fish status (fishless vs. fish bearing) in modulating historical food web response to dual forcing by bottom-up (resource regulation from nutrients) and top-down (planktivory from stocked fish) processes. We used the paleolimnological record to reconstruct food web changes in four lakes in interior British Columbia that have been stocked with rainbow trout since the early to mid-1900s. Analysis of pigments, diatoms, and Cladocera was undertaken in cores from all lakes. We predicted that if fish were important in structuring cladoceran abundance and composition, we would document a decline in the abundance of large daphnids post-stocking in our two naturally fishless lakes, and little change in the two fish-bearing lakes. Instead, we documented increased abundance of large daphnids after stocking in all lakes in the early to mid-1900s, a finding inconsistent with size-selective predation from planktivorous fish. Further, our data suggest that deep, low-oxygen refugia may be important in sustaining populations of large Daphnia , a process which was enhanced by increased nutrients and lake production according to sub-fossil diatom and pigment analyses. This study shows that fish stocking does not invariably result in a decrease in large-bodied Cladocera and that nutrients and lake type can modulate the response of invertebrate planktivores.

Surfactin-producing Bacillus velezensis 1B-23 and Bacillus sp. 1D-12 protect tomato against bacterial canker caused by Clavibacter michiganensis subsp. michiganensis - Matthew Laird; David Piccoli; Brian Weselowski; Tim McDowell; Justin Renaud; Jacqueline MacDonald; Ze-Chun Yuan (Journal of Plant Pathology, 2020)

Regional climate changes drive increased scaled-chrysophyte abundance in lakes downwind of Athabasca Oil Sands nitrogen emissions - Graham R. Mushet; Kathleen R. Laird; Biplob Das; Brittany Hesjedal; Peter R. Leavitt; Kenneth A. Scott; Gavin L. Simpson; Björn Wissel; Jared D. Wolfe; Brian F. Cumming (Journal of Paleolimnology, 2017)

Water depth is a strong driver of intra-lake diatom distributions in a small boreal lake - Cale A. C. Gushulak; Kathleen R. Laird; Joseph R. Bennett; Brian F. Cumming (Journal of Paleolimnology, 2017)

A Comparative Assessment of Arsenic Risks and the Nutritional Benefits of Fish Consumption in Kuwait: Arsenic Versus Omega 3-Fatty Acids - Adnan Husain; Kurunthachalam Kannan; Hing Man Chan; Brian Laird; Hanan Al-Amiri; Basma Dashti; Anwar Sultan; Amani Al-Othman; Bedraya Mandekar (Archives of Environmental Contamination and Toxicology, 2017)

Siliceous microfossil changes in impact and reference lakes in the uranium mining region of the Athabasca basin in northern Saskatchewan - Kathleen R. Laird; Biplob Das; Brian F. Cumming (Journal of Paleolimnology, 2015)

Augmentation of Normal and Glutamate-Impaired Neuronal Respiratory Capacity by Exogenous Alternative Biofuels - Melissa D. Laird; Pascaline Clerc; Brian M. Polster; Gary Fiskum (Translational Stroke Research, 2013)

Paleolimnological assessment of limnological change in 10 lakes from northwest Saskatchewan downwind of the Athabasca oils sands based on analysis of siliceous algae and trace metals in sediment cores - Kathleen R. Laird; Biplob Das; Melanie Kingsbury; Melissa T. Moos; Sergi Pla-Rabes; Jason M. E. Ahad; Brendan Wiltse; Brian F. Cumming (Hydrobiologia, 2013)

Assessment of drought over the past two millennia using near-shore sediment cores from a Canadian boreal lake - Heather A. Haig; Melanie V. Kingsbury; Kathleen R. Laird; Peter R. Leavitt; Robyn Laing; Brian F. Cumming (Journal of Paleolimnology, 2013)

Expanded spatial extent of the M edieval C limate A nomaly revealed in lake‐sediment records across the boreal region in northwest O ntario - Kathleen R. Laird; Heather A. Haig; Susan Ma; Melanie V. Kingsbury; Thomas A. Brown; C. F. Michael Lewis; Robert J. Oglesby; Brian F. Cumming (Global Change Biology, 2012)
Multi‐decadal to centennial‐scale shifts in effective moisture over the past two millennia are inferred from sedimentary records from six lakes spanning a ~250 km region in northwest O ntario. This is the first regional application of a technique developed to reconstruct drought from drainage lakes (open lakes with surface outlets). This regional network of proxy drought records is based on individual within‐lake calibration models developed using diatom assemblages collected from surface sediments across a water‐depth gradient. Analysis of diatom assemblages from sediment cores collected close to the near‐shore ecological boundary between benthic and planktonic diatom taxa indicated this boundary shifted over time in all lakes. These shifts are largely dependent on climate‐driven influences, and can provide a sensitive record of past drought. Our lake‐sediment records indicate two periods of synchronous signals, suggesting a common large‐scale climate forcing. The first is a period of prolonged aridity during the M edieval C limate A nomaly ( MCA , c. 900‐1400 CE ). Documentation of aridity across this region expands the known spatial extent of the MCA megadrought into a region that historically has not experienced extreme droughts such as those in central and western north A merica. The second synchronous period is the recent signal of the past ~100 years, which indicates a change to higher effective moisture that may be related to anthropogenic forcing on climate. This approach has the potential to fill regional gaps, where many previous paleo‐lake depth methods (based on deeper centrally located cores) were relatively insensitive. By filling regional gaps, a better understanding of past spatial patterns in drought can be used to assess the sensitivity and realism of climate model projections of future climate change. This type of data is especially important for validating high spatial resolution, regional climate models.

Graham Merrington, Ilse Schoeters (eds): Soil Quality Standards for Trace Elements: Derivation, Implementation, and Interpretation - Brian Laird (Ecotoxicology, 2011)

Diatom habitats, species diversity and water-depth inference models across surface-sediment transects in Worth Lake, northwest Ontario, Canada - Kathleen R. Laird; Melanie V. Kingsbury; Brian F. Cumming (Journal of Paleolimnology, 2010)

Nutrient Removal as a Function of Corn Stover Cutting Height and Cob Harvest - Jane M. F. Johnson; Wally W. Wilhelm; Douglas L. Karlen; David W. Archer; Brian Wienhold; David T. Lightle; David Laird; John Baker; Tyson E. Ochsner; Jeff M. Novak; Ardell D. Halvorson; Francisco Arriaga; et al. (BioEnergy Research, 2010)

Detectability of fifteen aquatic micro/mesocosms - Hans Sanderson; Brian Laird; Richard Brain; Christian J. Wilson; Keith R. Solomon (Ecotoxicology, 2009)

Diatom-inferred lake level from near-shore cores in a drainage lake from the Experimental Lakes Area, northwestern Ontario, Canada - Kathleen R. Laird; Brian F. Cumming (Journal of Paleolimnology, 2009)

Multidecadal to millennial‐scale shifts in drought conditions on the Canadian prairies over the past six millennia: implications for future drought assessment - ASTRID MICHELS; KATHLEEN R. LAIRD; SUSAN E. WILSON; DAVID THOMSON; PETER R. LEAVITT; ROBERT J. OGLESBY; BRIAN F. CUMMING (Global Change Biology, 2007)
Three high‐resolution climatic reconstructions, based on diatom analyses from lake sediment cores from the Canadian prairies, show that shifts in drought conditions have prevailed on centennial to millennial time scales for at least the past six millennia. These shifts in mean aridity exhibit broad regional synchrony, with particularly pronounced shifts at all sites between ∼1700–2000 cal. yr bp and ∼3600–3900 cal. yr bp , as well as at ∼5400–5500 cal. yr bp for the two sites which extend back to at least 6000 cal. yr bp . The two Saskatchewan lakes exhibited significant coherence in both the timing and direction of these shifts, whereas inferred changes at the westernmost site in Alberta were significantly correlated to the Saskatchewan sites, but opposite in sign, and exhibited more high‐frequency variation on the scale of centuries. The mechanisms behind these abrupt shifts in aridity are poorly understood, but may be linked to changes in oceanic–atmospheric interactions that influence the mean position of the jetstream and the associated storm tracks. Natural shifts in mean climatic conditions may accelerate with increasing carbon dioxide levels intensifying the likelihood of extreme droughts in North American prairies.

Surface Water Quality Impacts of Conservation Tillage Practices on Burley Tobacco Production Systems in Southwest Virginia - Brian L. Benham; Megan K. Laird; Blake B. Ross; David H. Vaughan; Danny R. Peek (Water, Air, & Soil Pollution, 2007)

Surface Water Quality Impacts of Conservation Tillage Practices on Burley Tobacco Production Systems in Southwest Virginia - Brian L. Benham; David H. Vaughan; Megan K. Laird; Blake B. Ross; Danny R. Peek (Water, Air, & Soil Pollution, 2007)

Diatom assemblages and water depth in Lake 239 (Experimental Lakes Area, Ontario): implications for paleoclimatic studies - Melissa T. Moos; Kathleen R. Laird; Brian F. Cumming (Journal of Paleolimnology, 2005)

A cladoceran-based paleolimnological assessment of the impact of forest harvesting on four lakes from the central interior of British Columbia, Canada - Emma L. Bredesen; Darren G. Bos; Kathleen R. Laird; Brian F. Cumming (Journal of Paleolimnology, 2002)

A 1500-year record of climatic and environmental change in ElkLake, Minnesota III: measures of past primary productivity - Platt Bradbury; Brian Cumming; Kathleen Laird (Journal of Paleolimnology, 2002)

A diatom-based reconstruction of drought intensity, duration, and frequency from Moon Lake, North Dakota: a sub-decadal record of the last 2300 years - Kathleen R. Laird; Sherilyn C. Fritz; Brian F. Cumming (Journal of Paleolimnology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)